Piecdziesieciu wielkich filozofow - Collinson, Diane, 1930-; Wyrzykowska, Malgorzata (Poznan : Zysk i S-ka, 1997)
Polish translation of "Fifty major philosophers, a reference guide". Biographies of 50 of the world philosophers who contributed the most to ourknowledge of the world and of ourselves.
Includes bibliographical references.
Keywords: Philosophy -- History; Philosophers -- Biography